Penerapan Manajemen Censorship di Perpustakaan UIN Raden Mas Said Surakarta - Mega Adjie Wikhda; Masruri, Anis; 'Azhim Al As'hal, Ajrun; Inayat, Muhammad (Media Informasi, 2025)
This research discusses the implementation of censorship management at UIN Raden Mas Said Surakarta Library as a strategy to control the procurement of collections that are not in accordance with academic needs and institutional values. Censorship is important because the library not only functions as an information provider, but also as a guardian of the quality and safety of content for users. The purpose of this study is to describe the process of applying censorship to library collections, as well as identify the obstacles faced by librarians in its implementation. This research uses a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation. The informants in this study were the censorship team consisting of the head of the library, librarians in the procurement section, and collection processing. The results showed that censorship activities have been implemented since the inception of the library and are carried out periodically every time there is a new collection procurement plan. The approach used refers to the McColvin model which combines the librarian's professional point of view and user needs. Some of the obstacles encountered include budget constraints, the high cost of foreign collections, and proposals for banned collections. Selective and structured censorship management is needed to maintain collection quality and support academic goals